Społeczne postrzeganie instytucji recall i weta ludowego w warunkach polskich - Marmola, Maciej (Political Preferences, 2015)
The social reception of recall and people’s veto among Polish electorate The institutions of direct democracy seem to be crucial for effective functioning of political system. The inclusion of citizens in decision-making process ensures that political representatives remain accountable throughout their term and must be responsive to the wishes of the voters. The empirical research conducted by the author proves that prevalent portion of electorate expects the introduction of recall and people's veto to Polish law. The results of analysis confirm the high level of citizens' support for institutions of direct democracy. This support is articulated by all groups of Polish electorate, regar- dless of party affiliation and ideological viewpoints. Key words: direct democracy, recall, people’s veto, social reception, Polish electorate